In vitro amplification and enhanced trans-species transmission of chronic wasting disease prions - Kurt, Timothy Daniel, author; Hoover, Edward A., advisor; Wilusz, Jeffrey, advisor (Colorado State University. Libraries, 2009)
Chronic wasting disease (CWD) is a prion disease of deer, elk and moose that is spreading rapidly in North America. Like all prion diseases, CWD is associated with conversion of a normal protein, PrPC, to a protease-resistant conformer, PrPRES (or PrPCWD). Little is known about the mechanisms of prion conversion or how it could lead to the rapid spread of CWD among cervids in nature. In this dissertation, I demonstrate the in vitro conversion of PrPC to PrPCWD via two protocols: non-denaturing amplification and serial protein misfolding cyclic amplification (sPMCA). Serial PMCA using brain substrate from transgenic mice that express cervid PrPC [Tg(CerPrP)1536 mice] produced PrPCWD amplification of >6.5 x 109-fold after six rounds. Efficient in vitro amplification of PrPCWD is a significant step toward potential ante-mortem detection of PrPCWD in CWD-infected animals. Whether CWD presents a threat to non-cervid species is not known. To predict non-cervid susceptibility to CWD, I used sPMCA to amplify PrP CWD in normal brain substrates from several non-cervid species. I show that brain homogenates from several CWD-susceptible species, such as ferrets and hamsters, support amplification of PrPCWD by sPMCA, whereas brain homogenates from CWD-resistant species, such as laboratory mice and transgenic mice expressing human PrPC, do not. Three common rodent species (including prairie voles and field mice) that share the environment with infected cervids supported PrPCWD amplification, whereas several other species (including prairie dogs, cats and coyotes) did not. Analysis of PrP sequences suggests that ability to support amplification of PrPCWD in trans-species sPMCA correlates with the presence of asparagine at position 170 of the substrate species PrP. I then inoculated CWD from deer into prairie voles (Microtus ochrogaster) and found they are somewhat susceptible to CWD. Inoculation of prairie voles with trans-species sPMCA products resulted in shorter and more consistent incubation periods. Furthermore, immunohistochemical analysis revealed an altered pattern of CWD prion deposition in infected voles compared to infected Tg(CerPrP)1536 mice, suggesting a different CWD strain. These results indicate that sPMCA can be used to increase PrPCWD detection sensitivity, predict susceptibility to CWD, accelerate adaptation in non-cervid species, and create new strains of CWD.
Keywords: chronic wasting disease; prion diseases; protein misfolding; transspecies transmission; pathology; virology